PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, KOMITE AUDIT DAN KOMISARIS INDEPENDEN TERHADAP TARIF PAJAK EFEKTIF (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Sulistyani Utari, 15.05.52.0030; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the influence of Firm Size, Leverage, Profitability, Audit Committee, Independent Commissioner on the Effective Tax Rate. This study focused on manufacturing companies listed on the Indonesia Stock Exchange. Determination of the sample was made by applying the purposive sampling method. The sample of this observation amounted to 66 companies listed in Indonesia Stock Exchange in the period 2015-2017 with the amount of data processed as many as 176. The influence between variables is explained using multiple regression analysis methods. The results showed that the Firm Size and Audit Committee has a negative effect, but not significant on Effective Tax Rate. Independent Commissioners has a positive effect, but not significant on Effective Tax Rate. While Leverage has a positive and significant effect on Effective Tax Rate, and Profitability has a negative and significant effect on Effective Tax Rate (ETR).